Algeria : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that the overall budget balance of Algeria weakened in 2001 and the first half of 2002. This deterioration mainly reflected higher spending and a decline in hydrocarbon revenues owing to a reduction in volumes and prices. The overall balance dropped from a surplus of 9.8 percent of GDP in 2000 to a surplus of 3.4 percent of GDP in 2001 and to a small deficit in the first half of 2002. Regarding structural reforms, some progress has been achieved in two areas: economic liberalization and privatization/public sector restructuring.